Valorization of Tomato Processing Residues Through the Production of Active Bio-Composites for Packaging Applications - Bugatti, Valeria; Brachi, Paola; Viscusi, Gianluca; Gorrasi, Giuliana (Frontiers in Materials, 2019)
The present work reports a study aimed at investigating the recovery and the upgrade of tomato processing residues through the preparation of innovative green composites based on tomato peels (TPs) and natural halloysite nanotubes (HNTs) loaded with carvacrol, as a natural antibacterial agent. The loading of carvacrol into HNTs was successfully achieved through a simple procedure that does not involve any chemical modifications of HNTs. Composite films with different amount of HNTs (i.e., 2.5, 5, 10, 20 %wt.) were prepared using mechanical milling in presence of water, followed by solvent casting method. The structural organization and the main physical properties of the obtained bio-based active composites have been deeply investigated. In particular, thermal and mechanical properties along with the films’ interaction with water vapor were assessed and then correlated to the filler loading. The thermal behavior of the composites resulted improved with filler loading. Mechanical properties showed a decrease of all the mechanical parameters, due to a lack interaction between HNTs and matrix, especially at high loading. The sorption of water vapour, analyzed at different relative humidities (24%, 55%, 80%), increased with increasing the moisture. The release of carvacrol was also analyzed. Results show that the obtained composites exhibit a long-term release of the antimicrobial agent, which suggests them as a promising candidate materials for food packaging application.